MODELING OF MONOCRYSTALLINE MAGNESIUM MICROBEAM BENDING - Jiří Němeček; Jan Maňák; Jiří Němeček (Acta Polytechnica CTU Proceedings)
This paper presents a numerical simulation of a micro-scale experiment on a magnesium alloy. Micro cantilever beams were fabricated using Focused Ion Beam technology in a single crystal of Mg. The cantilever beams have dimensions in the order of a few micrometers and a pentagonal cross section. Nanoindenter was used for cantilever beam bending and load-displacement curve was received. Cantilevers with two different crystallographic orientations were chosen for the experiment. Three dimensional numerical FE model with elastoplastic behavior respecting crystal anisotropy was used to fit experimental load displacement curves. Strengths and deformation energy were evaluated from the models for each cantilever.